A microRNA-initiated DNAzyme motor operating in living cells - Peng, Hanyong; Li, Xing-Fang; Zhang, Hongquan; Le, X. Chris (Nature communications, 2017)
Synthetic DNA motors have great potential to mimic natural protein motors in cells but the operation of synthetic DNA motors in living cells remains challenging and has not been demonstrated. Here we report a DNAzyme motor that operates in living cells in response to a specific intracellular target. The whole motor system is constructed on a 20 nm gold nanoparticle (AuNP) decorated with hundreds of substrate strands serving as DNA tracks and dozens of DNAzyme molecules each silenced by a locking strand. Intracellular interaction of a target molecule with the motor system initiates the autonomous walking of the motor on the AuNP. An example DNAzyme motor responsive to a specific microRNA enables amplified detection of the specific microRNA in individual cancer cells. Activated by specific intracellular targets, these self-powered DNAzyme motors will have diverse applications in the control and modulation of biological functions. Synthetic DNA nanomachines have been designed to perform a variety of tasks in vitro . Here, the authors build a nanomotor system that integrates a DNAzyme and DNA track on a gold nanoparticle, to facilitate cellular uptake, and apply it as a real-time miRNA imaging tool in living cells.